2.9 Exercises: Chapter 2

  1. Lindley’s paradox

  2. Given \(y_i\stackrel{iid}{\sim}N(\mu,\sigma^2)\) where \(p(\mu,\sigma)\propto 1/\sigma\). To test \(H_0. \ \mu=\mu_0\) vs \(H_1. \ \mu \neq \mu_0\). Given that \(\pi(\mu|\mathbf{y}, \mathcal{M}_1)=t\left(\bar{y},\frac{\hat{\sigma}^2}{N}\left(\frac{\alpha_n}{\alpha_n-2}\right),\alpha_n\right)\) where \(\alpha_N=N-1\) and \(\hat{\sigma}^2=\frac{\sum_{i=1}^N (y_i-\bar{y})^2}{N-1}\). Show that

\(p(\mathbf{y}|\mathcal{M}_1)=\frac{\pi^{-N/2}}{2}\Gamma(N/2)\left(\frac{1}{\alpha_n\hat{\sigma}^2}\right)^{N/2}\left(\frac{N}{\alpha_n\hat{\sigma}^2}\right)^{-1/2}\frac{\Gamma(1/2)\Gamma(\alpha_n/2)}{\Gamma((\alpha_N+1)/2)}\) and \(p(\mathbf{y}|\mathcal{M}_0)=(2\pi)^{-N/2}\left[\frac{2}{\Gamma(N/2)}\left(\frac{N}{2}\frac{\sum_{i=1}^N(y_i-\mu_0)^2}{N}\right)^{N/2}\right]^{-1}\). Then,

\[\begin{align} BF_{01}=\frac{p(\mathbf{y}|\mathcal{M}_0)}{p(\mathbf{y}|\mathcal{M}_1)}=\frac{\Gamma((\alpha_n+1)/2)}{\Gamma(1/2)\Gamma(\alpha_N/2)}(\alpha_n\hat{\sigma}^2/N)^{-1/2}\left[1+\frac{(\mu_0-\bar{y})^2}{\alpha_n\hat{\sigma}^2/N}\right]^{-\left(\frac{\alpha_n+1}{2}\right)}. \end{align}\]